BILATERAL SELF-ENUCLEATION IN THE FIRST PSYCHOSIS EPISODE IN A PERSON WITH DEPRIVED OF LIBERTY: CASE REPORT - Daniela Arias Mariño; Alejandro Rojas Urrea; Tania Astrid Adame; Lyanne Paola Mesa Huerfano; Lorena García Agudelo (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Introduction – Self-mutilation is an uncommon manifestation of diverse mental disorders and is more frequent in the first psychotic episode. The ocular, genital, and limb regions are the main areas affected. Methods – Presented the case of a 25-year-old male deprived of liberty who committed bilateral self-enucleation using a razor blade secondary to a first psychosis episode. Results – Patient did the auto-mutilation associated with magical and religious delusions, but there was no clinical evidence to consider it an organic mental disorder. Discuss – Self-multilation during the first episode of psychosis is highly related to schizophrenia spectrum pathologies. Delusions, especially auditory delusions and substance abuse, should be a red flag of psychosis. Conclusion – Knowledge about the consequences of psychiatric pathologies has a relevant impact on morbidity and mortality, especially in vulnerable populations. The case demonstrated the necessity of prompt treatment and psychiatric intervention to avert personal and non-personal injuries. Keywords: self-enucleation, self-mutilation, psychosis, self-harm, case report.